PERCEPTION OF THE QUALITY OF THE FINANCIAL SERVICES OF AUTONOMOUS DECEN-TRALIZED MUNICIPAL GOVERNMENT OF RIOBAMBA - Arguello Erazo, Stalin Efrén; Arellano Díaz, Mario Alfonso; Chafla Granda, Jorge Luis; Arguello Erazo, Mayra Lucrecia (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
The public institutions offer a series of services to the local population where they have their competences, among them are the financial services with the present investigation, the intention is to analyze the perception that users have of the financial services provided by the Municipal Decentralized Autonomous Government of the canton Riobamba. To measure this perception about the services provided in the financial environment, the SERVQUAL model was taken as a basis, for which there are 5 dimensions, to which the questions for each dimension were adapted. The research was descriptive and explanatory, whose design was non-experimental with a cross-sectional study since the surveys were carried out only once, the sampling was a simple probabilistic random, within this study 383 surveys were conducted on the Economically Active Population of the city of Riobamba as direct beneficiaries of the intervention of the Autonomous Government. Obtaining as one of the main results that 33.2% of respondents expressed reliability in the attention of financial services, which is why it qualifies as good.